Analyzing vertical mergers with auctions upstream - Joseph U. Podwol; Alexander Raskovich (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2021)
We develop a model of vertical mergers with open auctions upstream, This setting may be appropriate for industries where inputs are procured via auction-like "requests for proposal." For example, Drennan et al (2020) reports that a model of this type was used during the CVS-Aetna merger investigation, Our approach contrasts with a growing body of work on vertical mergers where input prices are determined through Nash bargaining, We discuss how the vertical merger effects of raising rivals' costs and eliminating double markup might be quantified in our particular model.
Keywords: 330